Global consumption of threatened freshwater eels revealed by integrating DNA barcoding, production data, and trade statistics - Kenzo Kaifu; Yu-San Han; Hiromi Shiraishi (Scientific Reports)
Abstract Fisheries resources depend on natural ecosystems, yet their sustainable management is often limited by uneven regional capacities and the pressures of international trade. High demand from certain regions can lead to overexploitation in others, highlighting the need to understand global consumption patterns of key aquatic species. This study introduces an integrated approach that combines DNA barcoding of freshwater eel (Anguilla spp.) products collected from end markets in 11 countries/regions with global production and trade statistics. We estimate that over 99% of eels consumed worldwide belong to three IUCN-listed threatened species: the American eel, Japanese eel, and European eel. Consumption was heavily concentrated in East Asia—particularly China, Japan, and South Korea—where supply volumes far exceed those of other regions. Our approach yields the most comprehensive quantitative global estimate to date of eel species composition in consumption, offering essential insights for the conservation and sustainable management of this highly exploited group.